Effect of mesoporous carbon support nature and pretreatments on palladium loading, dispersion and apparent catalytic activity in hydrogenation of myrcene - R. Castro Contreras (2019)
The influence of the carbon support characteristics on Pd loading, dispersion and activity in Pd/C catalysts has been analyzed. Several carbon nanomaterials, including multi-walled CNTs, nitrogen-doped CNTs, sulfur-doped CNTs, large- and small-diameter nanofibers, few-layer graphene, and a fibrous carbon have been produced, functionalized, defunctionalized and characterized using several techniques (e.g., nitrogen adsorption, Raman spectroscopy, XPS, TGA, and elemental analysis). These supports present different surface chemistry, arising from different features (defect concentration, inter-defect distances, longrange order, and orientation of the graphene layers) and specific surface areas. The most relevant parameters were obtained by characterization of the materials by Raman, XPS, nitrogen adsorption, and XRD. Twenty-four palladium catalysts with the same nominal loading (2%w/w) were prepared by wet impregnation using an acetone solution of Pd nitrate. These 24 catalysts were characterized by ICP, XRD, XPS and TEM. The final Pd loading varied between 1 and 2%w/w and the Pd particle size ranged from 1.5 to 3.3 nm, depending on the nature of the support. The parameters influencing both Pd loading and dispersion are discussed, and their very high activity for the myrcene complete hydrogenation are reported.